A rare case of Plasmodium (Haemamoeba) relictum infection in a free-living Red Knot (Calidris canutus rufa, Scolopacidae) - D'amico, Veronica Laura (2010)
The Red Knot (Calidris canutus rufa) is a Nearctic migrant shorebird that breeds in the Canadian Arctic and spends the winter season in coastal sites in South America. A rare case of a blood protozoan was found by molecular analyses from an adult bird captured during spring migration at the last refuelling stopover in Delaware Bay USA in 2006. The parasite was identified as Plasmodiumrelictum belonging to subgenus Haemamoeba based on the shape of meronts, roundish gametocytes, and its position in the erythrocytes from the blood smears examination. A partial cytochrome b sequence was a 100% match to a sequence of Plasmodium relictum, sequence Genbank accession number: id DQ659543.1 (lineage code haplotype P5). This is the first report of avian malaria in a wild individual of C. c. rufa.